Primary Cardiac Tumours: Our Experience - Sharma, J; Sherchan, S; Pradhan, S; Rajbanshi, B; Koirala, R; Tamala, R; Pokharel, J; Uprety, MR; Koirala, B (Nepalese Heart Journal, 2013)
Introduction Primary cardiac tumours are rare with autopsy incidence of less than 0.1 percent. We present our experience on surgical treatment of such tumours. Methods Since 2001, fifteen patients underwent surgical intervention for primary cardiac tumour at our centre. Mean age was 46.5 ± 17.5 years (range 20 to 73 years). There were eight female patients. Thirteen patients had atrial myxoma and the remaining two had primary malignant tumours. Surgical excision of the tumour was done under cardiopulmonary bypass and cardioplegic cardiac arrest. Results Complete excision was possible in all benign cardiac tumours where as excision was possible in only one of the two malignant tumours. One patient with suspected angiosarcoma had biopsy taken from the heart. There was no operative mortality. All the patients with atrial myxoma were symptom free and free of recurrence on follow-up echocardiography. The patient with suspected angiosarcoma (histopathology was reported as hemangioma only) presented with disseminated disease and metastasis to thoracic spine with paraplegia three months postoperatively. The other patient with rhabdomyosarcoma who had complete excision of tumour followed by repair of the defect is currently on adjuvant chemotherapy. Conclusion Surgical excision of primary benign cardiac tumours is possible with excellent surgical outcome where as outcome is guarded in primary malignant cardiac tumours. DOI: http://dx.doi.org/10.3126/njh.v8i1.8329 Nepalese Heart Journal Vol.8(1) 2011 pp.8-11